A COMPARATIVE STUDY TO OBSERVE THE SAFETY AND EFFICACY OF ULTRAFILTRATION VERSUS INTRA VENOUS DIURETIC DURING VALVULAR HEART SURGERY (Journal of Pharmaceutical Negative Results, 2023)
To study the efficacy and safety of ultra filtration versus intravenous diuretics for patients undergoing valvular heart surgery.